Long-Term Efficacy and Toxicity of Cholinesterase Inhibitors in the Treatment of Alzheimer Disease - Hogan, David B (Can J Psychiatry, 2014)
Though the symptoms of Alzheimer disease go on for years, the phase 3 trials of the cholinesterase inhibitors (ChEIs), the current mainstay of symptomatic pharmacotherapy for this condition, were typically of only 3- to 6-months’ duration. We have limited data on long-term (that is, a year or more) therapy with these agents. In this review, we explore the available information on the biological and clinical effects of long-term ChEI therapy, what happens when these agents are discontinued, and examine what others have recommended. An individualized approach to deciding on whether to carry on with a ChEI should be taken. If continued, treatment goals should be clarified and patients monitored over time, for both drug-related benefits and adverse effects.